2015
DOI: 10.1371/journal.pone.0135188
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Renal Dysfunction among HIV-Infected Patients on a Tenofovir-Based First Line Antiretroviral Treatment Regimen in Myanmar

Abstract: BackgroundSince 2004, Médecins Sans Frontières-Switzerland has provided treatment and care for people living with HIV in Dawei, Myanmar. Renal function is routinely monitored in patients on tenofovir (TDF)-based antiretroviral treatment (ART), and this provides an opportunity to measure incidence and risk factors for renal dysfunction.MethodsWe used routinely collected program data on all patients aged ≥15 years starting first-line TDF-based ART between January 2012 and December 2013. Creatinine clearance (CrC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 17 publications
4
23
1
Order By: Relevance
“…We found that older age (>50 years), lower pre-TDF eGFR (<60 ml/min/1.73m 2 ) and PI-based regimen are associated with higher risk of renal dysfunction in multivariate analysis, all of which were compatible with previous studies and the WHO recommendations for regular S-Cr monitoring [10,1921,24]. The higher risk in older age and lower pre-TDF eGFR can be explained by the fact that the CKD prevalence rises with age due to the increasing prevalence of risk factors for CKD, such as diabetes and hypertension, and the natural decline of renal function associated with aging [25].…”
Section: Discussionsupporting
confidence: 89%
“…We found that older age (>50 years), lower pre-TDF eGFR (<60 ml/min/1.73m 2 ) and PI-based regimen are associated with higher risk of renal dysfunction in multivariate analysis, all of which were compatible with previous studies and the WHO recommendations for regular S-Cr monitoring [10,1921,24]. The higher risk in older age and lower pre-TDF eGFR can be explained by the fact that the CKD prevalence rises with age due to the increasing prevalence of risk factors for CKD, such as diabetes and hypertension, and the natural decline of renal function associated with aging [25].…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, a 10 year follow-up cohort study of HIV-positive patients, reported that the quantified loss in eGFR attributable to Tenofovir was relatively modest after many years of exposure [12]. Since the majority of our patients had been on ART for more than 9 years, our failure to find an association between renal dysfunction and duration on Tenofovir containing ART can be explained by previous studies that reported that the loss in eGFR attributable to Tenofovir seemed to occur during the first years of exposure between 0.5 and 31.2 months and stabilized after that [16, 17, 2528]. Post marketing studies reported advanced age, low body weight, comorbidities such as diabetes mellitus, hypertension, as some of the risk factors for Tenofovir induced renal dysfunction [27, 29, 30].…”
Section: Discussionmentioning
confidence: 77%
“…However, we found no differences in glomerular function between patients who were on Tenofovir containing ART and those who were on Non-Tenofovir containing ART. Other studies have similarly reported no or minimal reductions in glomerular filtration rate among patients on Tenofovir [17, 21, 25]. Similarly, a 10 year follow-up cohort study of HIV-positive patients, reported that the quantified loss in eGFR attributable to Tenofovir was relatively modest after many years of exposure [12].…”
Section: Discussionmentioning
confidence: 99%
“…In the core group meeting between national programs for VL and HIV/AIDS, consensus was made on developing clearer recommendations and convergence between WHO ART guidelines and VL guidelines. Furthermore MSF is planning to do a clinical trial in collaboration with national health authorities to generate further robust evidence for best treatment options for HIV-VL co-infected patients in India.’ Kyaw N. et al (2015), Myanmar [30]The study used routinely collected programme data on all patients aged ≥ 15 years starting first-line tenofovir-based ART between 2012 and 2013. Creatinine clearance was assessed at base line and 6 monthly and incidence of renal dysfunction was calculated.The low incidence of renal toxicity in the patient cohort suggests that routine assessment of creatinine clearance may not be needed and could be targeted to high risk groups if resources permit. ‘ The national program adopted the alternative low cost screening method (urine protein testing) for screening of renal dysfunction in patients taking tenofovir and now uses the creatinine test only in high risk patients.’ Contributed to existing evidence leading to scale up of interventions Dave P. et al (2015), India [31]This was a retrospective cohort study involving a review of electronic patient records maintained routinely under the National Tuberculosis Programme, Gujarat, India in 2013.Offering rapid drug susceptibility testing (DST) at diagnosis improved the treatment outcomes among patients with pulmonary tuberculosis. ‘ The study findings strengthened the evidence of the effect of rapid DST at diagnosis on treatment outcomes of TB patients, which reinforced the national policy and has contributed to scale up of rapid DST facilities in the country.’ Change in policy and/or practice at subnational level Shewade H. et al (2014), India [32]Mixed-methods study, quantitative component consisted of retrospective cohort study reviewing records of all presumptive MDR-TB patients between October 2012 and September 2013.…”
Section: Resultsmentioning
confidence: 99%
“…Strong evidence from a multi-centric study involving multiple stakeholders might well bring about a policy change by itself [30]. However, it is possible that, in a given context with favourable background evidence, a single study may precipitate the final decision for policy change.…”
Section: Discussionmentioning
confidence: 99%